Beyond Legalism in Maqasid Al-Shariah: Integrating Theology, Philosophy, and Law for Contemporary Global Governance - Sidiq Siadio; Dahyul Daipon; Novelantika (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2026)
This study responds to the lack of an integrated epistemological framework in Maqasid al-Shariah scholarship, where theological, philosophical, and legal dimensions are frequently treated as discrete and self-contained domains. Prevailing approaches tend to prioritize legal formalism or adopt fragmented disciplinary perspectives, thereby constraining the capacity of maqasid to address contemporary global concerns such as human rights, social justice, and ethical governance in a systematic manner. The article seeks to reconstruct Maqasid al-Shariah through an interdisciplinary epistemological framework that coherently integrates theology, philosophy, and law. Methodologically, the study employs qualitative conceptual analysis grounded in a maqasid-oriented epistemology, complemented by a critical–comparative examination of selected classical scholars (al-Ghazali, al-Shatibi, and Ibn Rushd) alongside representative contemporary maqasid discourses. The analysis is guided by clearly articulated conceptual criteria, including modes of theological legitimation, the role of philosophical rationality in ethical justification, and the degree to which maqasid is confined to juridical instrumentalization. The findings indicate that the persistent separation of these disciplines generates three analytically identifiable structural limitations: theological rigidity, philosophical marginalization, and legal reductionism. These categories are derived inductively from recurring patterns of reasoning and argumentation observed across the examined texts, rather than from a priori normative assumptions. Collectively, these limitations inhibit maqasid from operating as a dynamic, context-responsive, and globally relevant normative framework.This study contributes to maqasid scholarship by proposing a reconstructed model in which theology furnishes normative legitimacy, philosophy secures rational universality, and law operationalizes ethical principles within institutional and regulatory contexts. By clarifying both the epistemological foundations and the analytical basis of maqasid, the proposed model advances Maqasid al-Shariah as a comprehensive paradigm capable of engaging complex global ethical challenges beyond the confines of traditional legalism.